Das necessidades formativas aos sentidos e significados da formação continuada de professoras da educação infantil: um estudo de caso dos Centros Municipais de Educação Infantil de Goiânia (2013-2019) - Ximenes, Priscilla de Andrade Silva (2020)
The research, carried out within the scope of the Line of Knowledge and Educational Practices, presents as problematic the training needs in relation to the social meanings and personal meanings that teachers of Early Childhood Education attribute to the training processes experienced in the Municipal Education Network of Goiânia / GO. Its main objective is to apprehend the senses and meanings that Early Childhood Education teachers attribute to the experienced training processes. The study has as its epistemological foundation the historical dialectical materialism and Activity Theory. Leontiev's concept and structure of activity, and the individual / society dialectical unit, postulated by Marx, enabled us to understand the pedagogical activity (teaching-study) as a forming or triggering unit of teacher education. The research, of the exploratory case study type, had the research corpus constituted by the following sources: documental analysis of the teacher education policies and the political-pedagogical proposal of Early Childhood Education in the municipality, interviews and questionnaires with early childhood teachers from RME . The analysis points to the consonances and contradictions between the teacher education policies of the municipality and the educational needs of teachers of Early Childhood Education, among which we highlight: the influences of national teacher education policies in the political-pedagogical proposal of Early Childhood Education the prioritization of institutional needs to the detriment of the individual and collective needs of teachers, as a result of the implementation of BNCC, BNC for Teacher Training and other national programs and guidelines. In relation to the training processes, we apprehend the differentiation between sense and meaning postulated from a policy of teacher training and professionalization that (re) produces the contradictions of the productive system under the logic of capital. This differentiation constitutes a revealing element of the teachers' resistance to the current national educational project, engendered by neoliberal principles and bourgeois hegemony. The analyzes support the initial hypothesis of this thesis that the split between the social meaning and the personal meaning of continuing education occurs because the teachers do not find in the training actions the possibilities for satisfying their needs, which emerge in concrete historical-social contexts, having their social practice (teaching work) as the starting point and the ending point of the activity. We defend the importance of overcoming the rupture between the individual / collective / institutional training needs of early childhood teachers to propose training processes, with a view to change and social transformation, providing the objective conditions (material and immaterial) for training, the professional development of teachers and the transformation of pedagogical praxis, since only “revolutionary praxis” educates children, men and women, including, of course, teachers.